KONTEKSTUAL DALAM ARSITEKTUR: Adaptasi Bangunan di Komplek Gedung Negara Cirebon - Soewarno, Nurtati; Nurhidayah, Nurhidayah; Rahadian, Erwin Yuniar (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2022)
Abstract: Indonesia has various of cultural heritages, both from local and immigrant culture. Gedung Negara, which previous called Residency Building, is one of the Dutch colonial government legacies in Cirebon city. Since its founding in 1865 until now this building has several times changed its name and function. This encourages various changes, additions, demolitions and transformations as an effort to adapt to new functions. The problem occurs if there is no context between new buildings and Gedung Negara as a cultural heritage building. This paper aims to determine the adaptation of architectural style of new buildings to Gedung Negara. By observing, a description of the function, form and architectural style of the new buildings around the Gedung Negara is obtained. Is there any architectural context betweem new buildings and Gedung Negara? How will the adaptation of these new buildings be? The architectural style context between new buildings and heritage buildings is highly recommended so that the new building can coexist in harmony with the cultural heritage building. It is hoped that the change of functions will not eliminate the uniqueness of the Indische Empire style and the Gedung Negara as a cultural heritage building in Cirebon city should be preserved well.Abstrak: Indonesia memiliki berbagai warisan budaya, baik yang berasal dari budaya lokal maupun budaya pendatang. Gedung Negara yang semula bernama Gedung Karesidenan adalah salah satu warisan Pemerintah Kolonial Belanda di kota Cirebon. Sejak didirikan tahun 1865 hingga saat ini gedung ini telah mengalami beberapa kali pergantian nama dan fungsi. Hal ini mendorong terjadinya berbagai perubahan, penambahan, pembongkaran maupun transformasi sebagai upaya adaptasi terhadap fungsi barunya. Permasalahan terjadi apabila tidak ada konteks antara bangunan baru dengan Gedung Negara sebagai bangunan cagar budaya. Makalah ini bertujuan untuk mengetahui adaptasi bentuk dan gaya arsitektur bangunan-bangunan baru terhadap Gedung Negara. Dengan melakukan observasi diperoleh gambaran fungsi, bentuk dan gaya arsitektur bangunan-bangunan baru di sekitar Gedung Negara. Apakah ada konteks gaya arsitektur antara bangunan baru dengan Gedung Negara? Bagaimana bentuk adaptasi bangunan-bangunan baru tersebut? Konteks gaya arsitektur antara bangunan baru dengan bangunan cagar budaya sangat disarankan agar bangunan baru dapat bersanding harmoni dengan bangunan cagar budaya. Diharapkan alih fungsi tidak menghilangkan keunikan gaya Indische Empire dan Gedung Negara sebagai bangunan cagar budaya di kota Cirebon sudah selayaknya dilestarikan dengan baik.